2010
DOI: 10.1074/jbc.m110.179622
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Alternatively Spliced Transcript Variants of CLEC2D Gene

Abstract: Lectin-like transcript 1 (LLT1) encoded by CLEC2D gene is a C-type lectin-like molecule interacting with human CD161 (NKR-P1A) receptor expressed by natural killer cells and subsets of T cells. Using RT-PCR and sequencing, we identified several CLEC2D alternatively spliced transcript variants generated by exon skipping. In addition to the reported transcript variants 1 (LLT1) and 2, we identified a novel splice variant 4 and transcripts coding for putative soluble proteins. CLEC2D transcripts were detected pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 28 publications
6
76
0
Order By: Relevance
“…33 IHC and IF stainings with anti-LLT1 mAb revealed a predominant cytoplasmic staining pattern as well as a membranous staining, consistent with our previous data showing both intracellular and cell surface expression of LLT1 32,33 ( Fig. 1).…”
Section: Llt1 Identifies Gc B Cells In Human Tonsils and Reactive Lymsupporting
confidence: 79%
See 2 more Smart Citations
“…33 IHC and IF stainings with anti-LLT1 mAb revealed a predominant cytoplasmic staining pattern as well as a membranous staining, consistent with our previous data showing both intracellular and cell surface expression of LLT1 32,33 ( Fig. 1).…”
Section: Llt1 Identifies Gc B Cells In Human Tonsils and Reactive Lymsupporting
confidence: 79%
“…Immunofluorescence FFPE sections were deparaffinized, pre-treated and incubated with Mo anti-LLT1 mAb (2F1) 33 or isotype mIgG1 control (R&D) at 1 mg/mL followed by secondary biotinylated Do antiMo IgG as described above. Antibody binding was fluorescently stained using Vectastain and TSA labeled with Alexa-488.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4B). This complex structure supports the previous report that PILAR (KACL) cannot bind to CD161 (8,9) because Asp 152 of PILAR (KACL), which corresponds to Lys 169 of LLT1, probably disrupts the interaction with Glu 205 of CD161 (Fig. 4, B and C).…”
Section: Thermodynamic Properties Of the Cd161-llt1 Interactionthe Nosupporting
confidence: 78%
“…On the other hand, Aldemir et al (5) and Rosen et al (6) identified one of the KLR family members, the human lectin-like transcript-1 molecule (LLT1) (also referred to as CLEC2D) as a ligand for the human CD161, and this recognition inhibited the CD161 ϩ NK cell cytotoxicity. Another study reported that proliferation-induced lymphocyte-associated receptor (PILAR) (also named KACL/ CLEC2A) is a second ligand of human CD161 (7); however, recent reports using a tetramer staining technique revealed that PILAR cannot bind to CD161 but instead binds to NKp65, which also belongs to the KLR family (8,9).…”
mentioning
confidence: 99%